Directive Strategies in Czech Classroom Communication - Chejnová, Pavla (Bohemistyka, 2026)
The study analyses teachers’ directive utterances recorded during spontaneous classroom interactions in Czech schools with pupils aged 11–16. Transcripts from the AKCES 2 corpus were examined using a coding scheme based on speech act theory. Teachers employed a range of communicative strategies, most of them direct. Imperatives were the most frequent, alongside performative verbs and modal constructions. Numerous non-sentential forms, such as adverbs, interjections, and elliptical expressions, also served directive functions. Teachers varied grammatical features like tense, person, and number to express politeness, reduce imposition, and achieve communicative efficiency.